2020
DOI: 10.1101/2020.03.09.983270
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visualizing protein-protein interactions in plants by rapamycin-dependent delocalization

Abstract: One-sentence summary: rapamycin-dependent delocalization allows quantifying proteinprotein interactions inside plant cells. Author contributions: DVD initiated the project and designed experiments. JW, EM, ADM and PG designed and performed experiments. BP wrote the script for quantification of the data. JM performed experiments. JW, PG and DVD wrote the paper. AbstractIdentifying protein-protein interactions (PPI) is crucial to understand any type of biological process. Many PPI tools are available, yet only s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 116 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…To address the TML-TPLATE interaction, we utilized the recently developed knocksideway assay in plants (KSP) (Winkler et al, 2020). KSP uses the ability of rapamycin to change the localization of a bait protein and its interacting partner via hetero-dimerization of the FK506-binding protein (FKBP) and the rapamycin-binding domain of mTOR (FRB).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To address the TML-TPLATE interaction, we utilized the recently developed knocksideway assay in plants (KSP) (Winkler et al, 2020). KSP uses the ability of rapamycin to change the localization of a bait protein and its interacting partner via hetero-dimerization of the FK506-binding protein (FKBP) and the rapamycin-binding domain of mTOR (FRB).…”
Section: Resultsmentioning
confidence: 99%
“…Using KSP, it was previously shown that full-length TPLATE can re-localize together with full-length TML. Furthermore, this tool allowed visualization of the ternary interaction between LOLITA, TASH3 and TPLATE ( 21 ). To this end, we transiently co-expressed various full-length and domain constructs of TML and TPLATE fused either to FKBP-mCherry or GFP, together with mitochondria-targeted FRB.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations